A New Paradigm for Testing Clinical Competence in Chaplaincy Certification. (March 2020) - Handzo, George F; Wintz, Susan K
This article describes the rationale, evolution, implementation, and evaluation of a process for testing clinical competence in health care chaplaincy certification. The process developed by the Spiritual Care Association uses Zoom technology, simulated patient actors, and evidence-based behaviors. Evaluation of the process by users has been very positive. The process seems to have acceptable validity, reliability, and usability and should be considered as an alternative to self-report clinical encounters as a test of clinical competence.